Aluminum surface nitriding by an atmospheric-pressure non-thermal plasma technique. (1st February 2022) - Ma, Zhongyang; Sun, Hongmei; Zheng, Huan; Zhao, Yanjun; Sui, Siyuan; Zhang, Chi; Ni, Guohua
Abstract: The application of aluminum is often limited by poor hardness, and plasma nitriding can make it have excellent mechanical properties. The purpose of this study is to nitride the aluminum surface by non-thermal transferred arc plasma technology. During the plasma nitriding process, the maximum effective value of output current is about 390 mA and the overall temperature of the samples is much lower than the solidus temperature. It is found that the microstructure and mechanical properties of the aluminum surface are improved by adding hydrogen into the nitrogen plasma. Compared with the surface treated by pure N2 plasma, the particle size of the aluminum surface treated by N2 /H2 plasma is smaller. The surface hardness of aluminum is nearly doubled after being treated in 6.0 vol% H2  + 94.0 vol% N2 atmosphere.